Dynamic Behavior of Materials, Volume 1 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Song, Bo; Lamberson, Leslie; Casem, Daniel; Kimberley, Jamie (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Dynamic Behavior of Materials, Volume 1 of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the first volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers on:  General Dynamic Material Response Fragmentation & Dynamic Fracture Large Scale Collaborative Facilities Dynamic Fracture and Failure Dynamic Behavior of Geo-materials Shock & Blast Novel Testing Techniques      .